Cyclic summation of roots of a cubic

Algebra Level 4

2 x 3 + x 2 7 = 0 \large 2x^3 + x^2 - 7 = 0

If α , β , γ \alpha, \beta, \gamma are the roots of the above equation, evaluate

cyc ( α β + β α ) \large \left | \displaystyle \sum_{\text{cyc}} \left( \dfrac{\alpha}{\beta} + \dfrac{\beta}{\alpha} \right )\right|

Note

  • z |z| is the absolute value of z z

  • cyc \displaystyle \sum_{\text{cyc}} means cyclic summation.


The answer is 3.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Hugh Sir
Jun 26, 2015

Note that α β + β γ + γ α = 0 \alpha\beta+\beta\gamma+\gamma\alpha = 0

cyc ( α β + β α ) = α 2 β + α 2 γ + β 2 α + β 2 γ + γ 2 α + γ 2 β α β γ \large \left | \displaystyle \sum_{\text{cyc}} \left( \dfrac{\alpha}{\beta} + \dfrac{\beta}{\alpha} \right )\right| = \large \left| \frac{{\alpha}^2\beta+{\alpha}^2\gamma+{\beta}^2\alpha+{\beta}^2\gamma+{\gamma}^2\alpha+{\gamma}^2\beta}{\alpha\beta\gamma} \right|

= ( α β + β γ + γ α ) ( α + β + γ ) 3 α β γ α β γ = \large \left| \frac{(\alpha\beta+\beta\gamma+\gamma\alpha)(\alpha+\beta+\gamma)-3\alpha\beta\gamma}{\alpha\beta\gamma} \right|

= 3 α β γ α β γ = \large \left| \frac{-3\alpha\beta\gamma}{\alpha\beta\gamma} \right|

= 3 = 3

Moderator note:

Is it possible to generalize this?

Emanuele Troiani
Jun 26, 2015

Given that α = a , β = b , γ = c \alpha = a, \beta=b, \gamma=c

Using Vieta's formulas you obtain these three equations:

a b c = 7 / 2 abc=7/2

a b + b c + a c = 0 ab+bc+ac=0

a + b + c = 1 / 2 a+b+c=-1/2

From the first equation we obtain that:

a b = 7 / 2 c ab=7/2c

b c = 7 / 2 a bc=7/2a

a c = 7 / 2 b ac=7/2b

This means that:

1 / a + 1 / b + 1 / c = 0 1/a+1/b+1/c=0

The solution is given by:

( 1 / a + 1 / b + 1 / c ) ( a + b + c ) = 0 (1/a+1/b+1/c)*(a+b+c)=0

a / b + b / a + a / c + c / a + b / c + c / b + a / a + b / b + c / c = 0 a/b+b/a+a/c+c/a+b/c+c/b+a/a+b/b+c/c=0

( a / b + b / a ) + ( a / c + c / a ) + ( b / c + c / b ) = 3 (a/b+b/a)+(a/c+c/a)+(b/c+c/b)=-3

3 = 3 \mid-3\mid=\boxed{3}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...